Prevalence of Under-Nutrition Measured by Composite Index of Anthropometric Failure (CIAF) Among the Bhumij Children of Northern Odisha, India - Goswami, Monali (Journal of Nepal Paediatric Society, 2016)
Introduction: Under-nutrition continues to be a serious health problem among the children in India. In view of the paucity of recent attempts to classify under-nourished children satisfactorily the Composite Index of Anthropometric Failure (CIAF) has been implemented to measure the seriousness and severity of overall under-nutrition in a population. However, there exists scanty information of the prevalence of under-nutrition among the tribal children of Odisha and India. Therefore the objective of the present study is to evaluate the overall prevalence of under-nutrition among the Bhumij children of Northern Odisha, India. Materials and Methods: A total of 136 Bhumij children aged 1 to 6 years (69 boys and 67 girls) were measured. Children were considered as underweight, stunting and wasting if their weight-for-age, height-for-age and weight-for-height Z-scores below -2.0 SD of the National Center for Health Statistics (NCHS) reference data. Severe under-nutrition was assessed as Z-score below -3.0 SD. Results: The overall age and sex combined prevalence of stunting, underweight and wasting recorded was 32.4%, 42.6% and 25% respectively, and these rates were considered as high (30-39%), very high (≥30%) and also very high (≥15%), respectively. CIAF showed a higher prevalence of undernutrition (54.4%) i.e., children suffering from anthropometric failure, in comparison to other three conventional indicators (stunting, underweight and wasting). Conclusions: Therefore various nutritional intervention programs can be formulated to improve the nutritional status of the children. It was established herein that CIAF is a better indicator of nutritional status than traditional measures of stunting, underweight and wasting because it differentiates overall and total anthropometric failure. J Nepal Paediatr Soc 2016;36(1):61-67